Adaptive management model of the higher education system in the context of the transition to the digital economy - R. V. Khuriev; F. A. Mambetova (Модернизация, инновация, развитие)
Purpose: of the study is to develop an adaptive model of higher education system management in the context of digital transformation of the economy.   Methods: the methods of interdisciplinary, structural and logical analysis, typologization of management models, rating and expert assessments were used in the work. The methodological basis of the research was: a three-sided model of higher education management assessment, a "management cube", including a model of new managerialism, a two-plane model of higher education system assessment, level-based, adaptive approaches to higher education management.   Results: based on the analysis of the higher education management system in the context of the digital transformation of the economy, the need for the formation of new adaptive mechanisms and management models of this system as an area where human capital is formed and developed, necessary for the breakthrough development of the country. Also, the trends of digitalization in the field of higher education have been identifi ed. Recommendations for its adaptation to the digital transformation of the economy have been developed and substantiated. As a key tool of the adaptive management model, an organizational model of adaptive management of the higher education system has been developed, which makes it possible to adapt the entire education system to the challenges of digital transformation of the economy.   Conclusions and Relevance: the developed organizational model will make it possible to build an eff ective work of the higher education system using adaptive management mechanisms, that allow it to optimally adapt to modern transformational processes, that occur according to cyclical crisis phenomena and the next industrial revolution. Digital transformation and the conditions of Industry 4.0, as well as the technological singularity, which is already the reality, do not allow us to strategically correctly build one specifi c model of management of the higher education system, since the above-mentioned processes become the trigger for constant transformations, including in the field of education. The organizational model of adaptive management proposed by the authors is innovative, allowing to adapt iteratively to the ongoing transformations of social and economic systems. Thus, this model is strategically relevant and promising for the both modern conditions of functioning and long-term development of the education sector.